Co‐winemaking with Vitis amurensis Rupr. "Beibinghong" enhances the quality of Vitis vinifera L. cv. Cabernet Gernischt wine. Issue 11 (27th September 2022) - Song, Jianqiang; Zhang, Ang; Cheng, Shiwei; Li, Xiuwei; Zhang, Yuxiang; Luan, Liying; Qu, Huige; Ruan, Shili; Li, Jiming
Abstract : Abstract: In some wine regions of China, Cabernet Gernischt (CG; Vitis vinifera L.) grape berries usually exhibit low pigment content and titratable acidity, and low sensory quality of the resulting wine. The aim of this study was to evaluate co‐winemaking of CG wines using the red grape cultivar Beibinghong (BBH; Vitis amurensis Rupr.) at different proportions in terms of alcohols, phenolic compounds, and sensory properties of the wines. The results showed that the co‐winemaking wines contained a similar content of higher alcohols, whereas the methanol content increased with an increase in BBH proportion, although this was still corresponded with the national standard. Significantly higher levels of titratable acidity were observed in co‐winemaking wines at the ratio of 6:4 and 5:5, compared with monocultivar CG wines. All co‐winemaking wines, except CG:BBH (9:1) wine, showed significantly higher levels of total anthocyanins, total phenolics, total tannins, and total flavan‐3‐ols. Further, individual phenolics, primarily diglucoside anthocyanins and non‐anthocyanins ( trans ‐ferulic acid, myricetin, viniferin, trans ‐caffeic acid, 3, 4‐dihydroxybenzoic acid), as important contributors to wine color intensity, permitted the differentiation of the wines via principal component analysis. In most cases, co‐winemaking wines exhibited higher scores of the 10 sensory attributes on color, aroma, mouthfeel, and overall quality compared with monocultivar wines. Co‐winemaking CG wines with BBH at 7:3 ratio demonstrated the highest scores of color intensity, aroma intensity, aroma quality, and overall quality. The results indicate that co‐winemaking with V. amurensis grape variety may be useful to enhance V. vinifera wine quality by modifying wine composition. Practical Application: Cabernet Gernischt (CG) is the predominant grape cultivar used to prepare premium‐quality wine in China; however, in some wine regions, CG wines have low levels of pigment and titratable acidity, and low sensory quality. Co‐winemaking with another native grape cultivar, Beibinghong (BBH), which is characterized by a higher content of anthocyanins and acidity, provided sufficient experimental evidence of adjustments in the Vitis vinifera wine composition leading to improved wine sensory quality.